Entrepreneurial Success Factors for Youth Entrepreneurs in the Era of Society 5.0 - Zuraidah, Zuraidah; Maudya, Intan Yhejri Rari; Mufidaturrohmah, Nur (International Journal of Business and Applied Economics, 2025)
This study examines young entrepreneurs' perceptions of factors influencing entrepreneurial success in the Society 5.0 era. Using a quantitative approach, data were collected from 72 Economics students from 2021 to 2023 at UIN Malang. Key variables include education, experience, strategy, innovation, and technology, which were analyzed using SmartPLS 3. The findings show that these factors significantly enhance entrepreneurial success, emphasizing their critical roles in fostering entrepreneurship. The study theoretically reinforces the importance of these elements in entrepreneurship. Practically, it suggests revising curricula to integrate practical experiences and advanced technologies while advising young entrepreneurs to focus on innovation and strategic planning. This research supports young entrepreneurs in navigating challenges and enriches the literature on entrepreneurship in the Society 5.0 era.